Assessment of the Safety of Transport of the Natural Gas–Ammonia Mixture - Andrzej Rusin; Katarzyna Stolecka-Antczak (Energies, 2023)
The decarbonisation of many sectors of the economy, including primarily the energy sector, results in the gradual elimination of hydrocarbon fuels, especially coal. During the transition period, it will be possible to use natural gas, the combustion of which is associated with lower carbon dioxide emissions. Further reduction in this emission is possible with the use of mixtures of natural gas with other gases, e.g., ammonia. Ammonia, widely used in many industries, has recently been described as the emission-free fuel of the future. However, both of these gases are hazardous substances. Natural gas is a flammable gas and ammonia is a toxic gas. This paper presents an assessment of the transport safety of natural gas (methane) and its mixture with ammonia. The uncontrolled release of these substances from a damaged gas pipeline may cause a fire or a toxic hazard. This work presents hazard zones arising in the event of such a failure and determines the impact of various mixture compositions on the level of the potential hazard. The level of risk related to the uncontrolled release of a mixture of natural gas and ammonia was analysed. It has been estimated that for pipelines with a diameter of 400 mm and a low-pressure mixture of methane and ammonia in the proportion of 50/50 v/v, the danger zone with the risk of loss of life above 1 × 10−3 is approximately 50 m. In the case of the same pipelines transmitting the mixture of these high-pressure gases, the high-risk zone may extend to approximately 175 m.